Immune Cell Profiling During Switching from Natalizumab to Fingolimod Reveals Differential Effects on Systemic Immune-Regulatory Networks and on Trafficking of Non-T Cell Populations into the Cerebrospinal Fluid—Results from the ToFingo Successor Study - Lohmann, Lisa; Janoschka, Claudia; Schulte-Mecklenbeck, Andreas; Klinsing, Svenja; Kirstein, Lucienne; Hanning, Uta; Wirth, Timo; Schneider-Hohendorf, Tilman; Schwab, Nicholas; Gross, Catharina C.; Eveslage, Maria; Meuth, Sven G.; et al. (Frontiers in Immunology, 2018)
Leukocyte sequestration is an established therapeutic concept in multiple sclerosis (MS) as represented by the trafficking drugs natalizumab and fingolimod. However, the precise consequences of targeting immune cell trafficking for immune-regulatory network functions are only incompletely understood. In the present study, we performed an in-depth longitudinal characterization of functional and phenotypic immune signatures in peripheral blood (PB) and cerebrospinal fluid (CSF) of 15 multiple sclerosis patients during switching from long-term natalizumab to fingolimod treatment after a defined 8-week washout period within a clinical trial (ToFingo successor study; ClinicalTrials.gov: NCT02325440). Unbiased visualization and analysis of high-dimensional single cell flow-cytometry data revealed that switching resulted in a profound alteration of more than 80% of investigated innate and adaptive immune cell subpopulations in the peripheral blood, revealing an unexpectedly broad effect of trafficking drugs on peripheral immune signatures. Longitudinal cerebrospinal fluid analysis demonstrated that natalizumab and fingolimod both reduced T cell subset counts and proportions in the cerebrospinal fluid of multiple sclerosis patients with equal potency; natalizumab however was superior with regard to sequestering non-T cell populations out of the cerebrospinal fluid, including B cells, NK cells and inflammatory monocytes, suggesting that disease exacerbation in the context of switching might be driven by non-T cell populations. Finally, correlation of our immunological data with signs of disease exacerbation in this small cohort suggested that both i) CD49d expression levels under natalizumab at the time of treatment cessation, and ii) swiftness of fingolimod-mediated effects on immune cell subsets in the peripheral blood together may predict stability during switching later on.